Fisher effect: evidence from money market in Malaysia - Zainal, Nurazilah; Md Nassir, Annuar; Yahya, Mohamed Hisham (Macrothink Institute, 2014)
The Fisher Effect, proposed by Fisher (1930), has been the subject of many empirical researches in various countries. In Malaysia, previous empirical studies on Fisher Effect have focused the relationship on stock and bond market, leaving the money market with no or very few studies. The Malaysian money market has gained importance and interests as it shows rapid growth in volume transaction. This paper aims at investigating the validity of Fisher Effect on Malaysian money market. The time series between 2000 to 2012 is chosen as the study duration. Three variables were targeted in this study, they are, inflation Rate (INF), 3-months treasury bills rate (MTB) and interbank rate (IBR). To study the relationship, this paper employs Autoregressive Distributed Lag (ARDL) bounds test that is capable of testing for the existence of a long-run relationship between the variables irrespective of whether the time series are I(0) or I(1). The estimation results indicate the presence of long run cointegration among the variables. Overall the study provides evidence on the Fisher Effect in Malaysia.